Enhancement of PKK Skills in Processing Local Food Rebon Shrimp Into Crackers: A Functional Food for Preventing Dental Caries - Gema Nazri Yanti; Gema Nazri Yanni; Etti Sudaryati (JURNAL ABDIMAS MADUMA, 2024)
Local food in Bagan Serdang Village, such as rebon shrimp rich in calcium, has significant potential for local utilization and marketing. Unfortunately, this potential is often hindered by a lack of community knowledge and skills. The community service team aims to enhance the understanding and skills of PKK members in processing local food to form economically and socially independent groups, producing products beneficial for health, especially oral health. Activities include socialization, education, and training, with results showing increased knowledge and skills among the participants in making local food products, such as rebon shrimp crackers Keywords : Rebon shrimp; Functional food; Dental caries; Crackers; Calcium